Physical growth and sexual maturation of perinatally HIV-infected adolescent males in a southeast Nigerian tertiary hospital: a comparative cross-sectional study - Chibuzo O Ndiokwelu; Samuel N Uwaezuoke; Kenechukwu K Iloh (BMC, 2022)
Abstract Background The advent of highly-active anti-retroviral therapy (HAART) has resulted in the survival of children with Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) into adolescence. Their prolonged survival has translated into co-morbidities like endocrine deficiencies which may manifest as growth and pubertal delay. This study aimed to determine the physical growth and sexual maturation of perinatally HIV-infected adolescent males and compare them with those of age-matched HIV-negative controls. Methods We conducted a comparative cross-sectional study of 104 perinatally HIV-infected males on HAART aged 10 to 19 years, and 104 age-matched HIV-negative males who served as controls. The subjects and controls were enrolled and assessed at a Nigerian tertiary hospital over six months. Anthropometric measurements such as weight, height, and BMI were obtained and Z scores for age were derived for weight, height, and BMI to determine physical growth using WHO AnthroPlus software. Sexual maturation was assessed using the method proposed by Marshall and Tanner. Data analysis and appropriate statistics were conducted with the Statistical Package for Social Sciences (SPSS) version 25 Chicago IL. A p-value < 0.05 was adopted as the level of statistical significance. Results The mean height, weight, and BMI Z scores of the subjects were all lower than those of the controls. The difference between the mean weight of the subjects (44.60 ± 13.32 kg) and the controls (49.97 ± 13.58 kg) was statistically significant (t = 2.88, p = 0.004). Similarly, the difference between the mean BMI Z-scores of the subjects (-0.96 ± 1.95) and the controls (-0.10 ± 0.86) was statistically significant (t = 4.10, p = < 0.001). The subjects showed a delay in pubic hair and testicular development for Stages 1, 2, and 3. Duration of HAART did not significantly affect the BMI of subjects who were in three groups: undernutrition, normal nutrition, and overnutrition (Kruskal-Wallis test, p = 0.30). Conclusion Perinatal HIV infection negatively affects physical growth and the onset of pubic-hair development (PH 2) despite the duration of HAART. We recommend that screening for weight deficit or pubertal delay should form part of the management protocol for HIV-infected male children on HAART.